Between risk and autonomy: producing subjects in group homes and supervised workshops for people with intellectual disabilities - Gappmayer, Georg (Disability & society, 2023)
This study focusses on the question of how the values of autonomy, self-determination, and independence influence people with intellectual disabilities who live in a social world of institutionalized care. It analyses policies and practices - everyday activities. Data collection took place during 240 h of participant observation in three group homes and one workshop for adults with intellectual disabilities in Austria. The analysis demonstrates that these organizations attempt to enhance the status of people cared for to that of an autonomous subject. But this project is failing, as these people do not have the practical knowledge required to fulfil the social demands of reason, responsibility for their actions and their physical integrity, and also to manage household tasks efficiently. Consequently, they assimilate to being dependent subjects. Two risk management strategies support this: everybody should be treated equally, plus the loss of responsibility outside the social world and in medical practices. Points of interest This article compares written guidelines and everyday activities in group homes and supervised workshops for people with intellectual disabilities in Austria. It wants to clarify the connections between everyday activities, disability, society, and personal aims. The written guidelines of institutions for people with intellectual disabilities support the idea that people should become more self-determined and independent. However, everyday activities reveal that in real life, it is more important to keep people safe and well-cared for. This mismatch also becomes visible in a conflict between the ideal that people in group homes should be autonomous and the demand that the caregivers minimize possible health risks. This study recommends accepting that all people are somehow dependent. Further, the aim of belonging to others should receive more attention in group homes and supervised workshops.